Regarding the sink : where, oh where, did Waters go? - Klise, Kate (Klise, Kate. Regarding the--, 2004)
A series of letters reveals the selection of the famous fountain designer, Florence Waters, to design a new sink for the Geyser Creek Middle School cafeteria, her subsequent disappearance, and the efforts of a class of sixth-graders to find her.